Research handbook on corporate crime and financial misdealing - Arlen, Jennifer H. (Research handbooks in corporate law and governance, 2018)
"This...handbook examines how to deter corporate misconduct through public enforcement and private interventions. Contributors present theoretical and empirical analyses of individual and organizational liability for corporate misconduct, securities, fraud and corruption. Other chapters evaluate private interventions, such as whistleblowing and compliance. Chapters cover individual and organizational liability issues such as individual liability for corporate crime, deferred and non-prosecution agreements, supervisory liability, the cost to organizations of reputational damage from corporate settlements, corporate and individual liability for securities fraud, the SEC's revolving door, multi-jurisdictional enforcement of anti-corruption laws, the scope of the Foreign Corrupt Practices Act, and countries' efforts to deter corruption by state actors. Chapters on private interventions examine optimal compliance, behavioral compliance, the role of the general counsel, internal investigations, and whistleblowing. This Research Handbook also highlights promising avenues for future research."--